Life Skills Education for Youth Critical Perspectives - DeJaeghere, Joan; Murphy-Graham, Erin (Young People and Learning Processes in School and Everyday Life, 2022)
This open access volume critically reviews a diverse body of scholarship and practice that informs the conceptualization, curriculum, teaching and measurement of life skills in education settings around the world. It discusses life skills as they are implemented in schools and non-formal education, providing both qualitative and quantitative evidence of when, with whom, and how life skills do or do not impact young women's and men's lives in various contexts. Specifically, it examines the nature and importance of life skills, and how they are taught. It looks at the synergies and differences between life skills educational programmes and the way in which they promote social and emotional learning, vocational/employment education, and health and sexuality education. Finally, it explores how life skills may be better incorporated into education and how such education can address structures and relations of power to help youth achieve desired future outcomes, and goals set out in the Sustainable Development Goals (SDGs). Life skills education has gained considerable attention by education policymakers, researchers and educators as being the sine qua non for later achievements in life. It is nearly ubiquitous in global and national education policies, including the SDGs, because life skills are regarded as essential for a diverse set of purposes: reducing poverty, achieving gender equality, promoting economic growth, addressing climate change, fostering peace and global citizenship, and creating sustainable and healthy communities. Yet, to achieve these broad goals, questions persist as to which life skills are important, who needs to learn them, how they can be taught, and how they are best measured. This book addresses these questions.